Pharmacological and toxicological effects of Amaryllidaceae - M. J. M. Paiva; G. N. L. Nascimento; I. A. M. Damasceno; T. T. Santos; D. Silveira (Brazilian Journal of Biology, 2023)
Abstract The Amaryllidaceae family is widely distributed in the tropics, presenting biological activity attributed mostly to alkaloids, such as an important inhibitory activity of acetylcholinesterase (AChE), antifungal, antibacterial, and cytotoxic activities. The present study aims to review the spectrum of action of the main biological activities and toxicity of secondary metabolites found in Amaryllidaceae through a literature review, using Prisma and the descriptors “Pharmacological effects of Amaryllidaceae” and “Amaryllidaceae family” and “Pharmacological actions of Amaryllidaceae”, used in English and Portuguese. The literature search was done in March and May 2023. Original works published from 2012 to 2023, available in full, and presenting experimental and clinical studies were included. After the selection considering the inclusion and exclusion criteria, 60 articles fulfilled the defined criteria. From a pharmacological point of view, the highlight is due to the alkaloid galantamine, which has the potential- and is already used - for treating Alzheimer's. The toxicological aspect must be considered and evaluated carefully, as alkaloids have been associated with adverse effects such as nausea, vomiting, diarrhea, abdominal pain, and cardiovascular, neurological, and respiratory changes. Furthermore, some studies indicate that consuming these plants in significant quantities can lead to hepatic and renal toxicity. Therefore, the therapeutical use of this family's plant drugs and derivatives requires further studies to elucidate its effects and point out metabolites with therapeutic potential.